2018
DOI: 10.3399/bjgpopen18x101541
|View full text |Cite
|
Sign up to set email alerts
|

Primary care for people with an intellectual disability — what is prescribed? An analysis of medication recommendations from the BEACH dataset

Abstract: BackgroundPeople with intellectual disability (ID) experience a range of health disparities. Little is known about differential primary care prescribing patterns for people with and without ID.AimTo compare medications recommended by GPs at encounters where ID is recorded versus other encounters.Design & settingAnalysis of national Australian GP medication data from the Bettering the Evaluation and Care of Health (BEACH) programme, January 2003–December 2012 inclusive.MethodMedication recommendations made at e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“… 4 , 74 , 75 In addition, a higher number of patients with ID are reported with psychotropic prescriptions than with recorded MHDs, indicating off-label prescription. 4 , 39 , 44 , 49 , 75 – 80 Behavioural problems are often described as an indication to start medication, 4 , 39 , 59 , 73 , 74 , 78 , 79 specifically in cases of limited access to alternative treatment strategies. 4 Prescribed medication is reported as predominantly long-term medication, 75 and a large proportion (62%–70%) is prescribed without a psychiatrist’s involvement.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 4 , 74 , 75 In addition, a higher number of patients with ID are reported with psychotropic prescriptions than with recorded MHDs, indicating off-label prescription. 4 , 39 , 44 , 49 , 75 – 80 Behavioural problems are often described as an indication to start medication, 4 , 39 , 59 , 73 , 74 , 78 , 79 specifically in cases of limited access to alternative treatment strategies. 4 Prescribed medication is reported as predominantly long-term medication, 75 and a large proportion (62%–70%) is prescribed without a psychiatrist’s involvement.…”
Section: Resultsmentioning
confidence: 99%
“…50 Indications of inaccurate diagnoses 48,51 and underdiagnosis in primary care are frequently reported 4,31,41,42,48,49,[52][53][54][55][56] and may result in inappropriate care and progression of the disorder to a more severe stage that is less responsive to treatment. 23,52,[57][58][59] Overdiagnosis, however, occurs as well, leading to unnecessary prescriptions of medication. 53,57 Diagnostic failure is seen as related to communication problems, with patients with ID described as less able to label their feelings and communicate their needs, 44,53,57,[60][61][62] resulting in an atypical presentation of symptoms 29,43,44,57,[63][64][65] and a more complicated assessment.…”
Section: Gp Rolesmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, the individuals included in this study were originally sequenced to diagnose the cause of ID in the children. Several studies have shown that polypharmacy is more common among patients with ID . More important, patients with ID more often use antipsychotics, anticonvulsants, and/or antidepressants that frequently result in gene–drug interactions making the value of a PGx profile for this population even more meaningful.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that polypharmacy is more common among patients with ID. [33][34][35] More important, patients with ID more often use antipsychotics, anticonvulsants, and/or antidepressants that frequently result in gene-drug interactions making the value of a PGx profile for this population even more meaningful. Unfortunately, many of these drugs are metabolized by either CYP2D6 or CYP2C19, both of which have shown to be difficult to determine based on existing WES data in our study.…”
Section: Articlementioning
confidence: 99%